Pengaruh Socially Responsible Investment Terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Undustri Barang Konsumsu yang Terdaftar di BEI Periode 2014-2018 - Maretta Paulakarin; Yulia Efni; Haryetti Haryetti (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
The aims of this research is to examine the effect of Socially Responsible Investment (SRI) towards the financial performance of the company. The population in this research are manufacturing company sector consumer goods industry listed on the Indonesia Stock Exchange (IDX) period 2014-2018, totaling 49 companies. Sampling using purposive sampling method, and obtained 170 data from 34 companies in each period. This research used Structural Equation Modeling-Partial Least Square (SEM-PLS) to analyze data. The results of research showed that Socially Responsible Investment (SRI) have a positive significant impact on the financial performance used firm size as control variabel. Financial perfomance in this researchs measured by Return on Asset (ROA), Return on Equity (ROE) dan Net Profit Margin (NPM). Socially Responsible Investment (SRI) measured by JSE Limited SRI Index 2019 and firm size measured by total assets, total sales and total employees.